2015
DOI: 10.1016/j.jaci.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the hygiene hypothesis for allergy and asthma

Abstract: The hygiene hypothesis, which describes the protective influence of microbial exposures in early life on the development of allergy and asthma, has continued its swell of academic interest, investigation, and evolution. This article is focused on studies published in the past 3 years that have furthered the substance and shape of hygiene theory, primarily as it relates to allergic airways and asthma. Recent investigations have furthered an overarching "microbiome hypothesis" to home features, medical practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 71 publications
(84 reference statements)
4
109
0
5
Order By: Relevance
“…Si bien no se realizó la distinción del agente etiológico viral en el presente estudio, lo más probable es que la mayoría de pacientes con exposición positiva, hayan tenido una infección por VSR. No tenemos datos epidemiológicos exactos en nuestro medio, pero en revisiones extranjeras se estima que, en menores de 2 años el VSR es el agente más frecuente en las infecciones virales del tracto respiratorio (14,16 tempranas en la infancia podrían disminuir la probabilidad de desarrollar SRRR ("Teoría de la higiene y atopia") (19), se sabe que los virus son potentes desencadenantes de exacerbaciones de esta enfermedad en todos los grupos etarios (1,18,20). Se ha demostrado también, que la bronquiolitis por VSR, si es temprana en la infancia y severa, podría incrementar el riesgo de episodios de sibilancias hacia la época escolar (11,12).…”
Section: Discussionunclassified
“…Si bien no se realizó la distinción del agente etiológico viral en el presente estudio, lo más probable es que la mayoría de pacientes con exposición positiva, hayan tenido una infección por VSR. No tenemos datos epidemiológicos exactos en nuestro medio, pero en revisiones extranjeras se estima que, en menores de 2 años el VSR es el agente más frecuente en las infecciones virales del tracto respiratorio (14,16 tempranas en la infancia podrían disminuir la probabilidad de desarrollar SRRR ("Teoría de la higiene y atopia") (19), se sabe que los virus son potentes desencadenantes de exacerbaciones de esta enfermedad en todos los grupos etarios (1,18,20). Se ha demostrado también, que la bronquiolitis por VSR, si es temprana en la infancia y severa, podría incrementar el riesgo de episodios de sibilancias hacia la época escolar (11,12).…”
Section: Discussionunclassified
“…Increasing numbers of studies have also shown that exposure to pets is not limited to allergens. Cats and dogs can alter the abundance, richness and/or diversity of host and home microbiome, which in turn may influence the development of a child’s immune system and responses to allergens, supporting the “hygiene hypothesis” [66, 6874]. While interactions between bacterial endotoxin and pet allergens have been most extensively studied [30, 75], research interests have expanded into more diverse microbial taxa [6872, 73••].…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 97%
“…Evidence to support this revised hygiene hypothesis includes observations of the low incidence of asthma in Amish populations in the US, as in this farming community, childhood contact with farm animals exposes them diverse microbiota 73 . The Prevention of Allergy-Risk Factors for Sensitization in Children Related to Farming and Anthroposophic Lifestyle (PARSIFAL) and Multidisciplinary Study to Identify the Genetic and Environmental Causes of Asthma in the European Community (GABRIELA) study groups describe decreased rates of asthma in children growing up in farms in central Europe, compared to children located in the same region not living on farms.…”
Section: Microbiome Exposure In Early Childhood Contributing To Asthmmentioning
confidence: 97%
“…The premise that sterile environments may predispose patients to asthma, while early childhood exposures to diverse microbial milieu prevents asthma acquisition, is the basis of the hygiene hypothesis 73 . The finding that greater microbial diversity is inversely related to airway hyper-responsiveness is congruent with the recent revision of the hygiene hypothesis that early life exposure to diverse microbes diminishes the risk of developing asthma 74 .…”
Section: Microbiome Exposure In Early Childhood Contributing To Asthmmentioning
confidence: 99%